A note on Baskakov‐Kantorovich type operators preserving e−x. (11th November 2018) - Yılmaz, Övgü Gürel; Gupta, Vijay; Aral, Ali
Abstract : In this paper, we give a generalization of the Baskakov‐Kantorovich type operators that reproduce functions e 0 and e − x . We discuss uniform convergence of this generalization by means of the modulus of continuity and establish quantitive asymptotic formula.